Filosofías de la composición (El Hilo de la Fabula, 2015)
This article focuses on two cases of narrative texts about the writing of a poem, the story “Shadows on Bevelled Glass” (1966) by the Argentine writer Juan José Saer and Hopeless (1984) by the Colombian writer Antonio Caballero. In both texts a tension between the stream of consciousness of the poet and the composition of the poem results in an epiphanic writing marked by tensions between the time of the events and the ecstatic nature of the poem.